Process improvement for reducing side discrepancies in radiology reports. (August 2018) - Digumarthy, Subba Rao; Vining, Rachel; Tabari, Azadeh; Nandimandalam, Sireesha; Otrakji, Alexi; Shepard, JoAnne O; Kalra, Mannudeep K
Background: Laterality errors in radiology reports can lead to serious errors in management. Purpose: To reduce errors related to side discrepancies in radiology reports from thoracic imaging by 50% over a six-month period with education and voice recognition software tools. Material and Methods: All radiology reports at the Thoracic Imaging Division from the fourth quarter of 2016 were reviewed manually for presence of side discrepancies (baseline data). Side discrepancies were defined as a lack of consistency in side labeling of any abnormality in the "Findings" to "Impression" sections of the reports. Process map and Ishikawa fishbone diagram (Microsoft Visio) were created. All thoracic radiologists were educated on side-related errors in radiology reports for plan–design–study–act cycle 1 (PDSA #1). Two weeks later, voice recognition software was configured to capitalize sides (RIGHT and LEFT) in the reports during dictated (PDSA# 2). Radiology reports were analyzed to determine side-discrepancy errors following each PDSA cycle (post-interventional data). Statistical run charts were created using QI Macros statistical software. Results: Baseline data revealed 33 side-discrepancy errors in 47, 876 reports with an average of 2.5 errors per week (range = 1–8 errors). Following PDSA #1, there were seven errors pertaining to side discrepancies over a two-week period. Errors declined following implementation of PDSA #2 to meet the target of 0.85 side-discrepancy error per week over seven weeks. Conclusion: Automated processes (such as capitalization of sides) help reduce left/right errors substantially without affecting reporting turnaround time.